Child Benefit Reform and Labor Market Participation - Marcus Tamm (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the impact of a change in the German child benefit system in 1996, which led to a large increase in lump sum transfers to families with children. We analyze the impact on the labor force participation of family members. Comparing behavioral changes of adults with children with behavioral changes of adults without children, we find that single mothers and mothers with a working partner considerably reduced the number of working hours (conditional on participation). Participation rates however did not decrease. For single fathers neither participation rates nor working hours display any significant changes.
Keywords: H31; I38; J22; 330; Child support; labor supply; program evaluation; Familienleistungsausgleich; Sozialreform; Wirtschaftspolitische Wirkungsanalyse; Arbeitsangebot; Deutschland